Using Positive Empathy Interventions to Reduce Stigma Toward People Who Inject Drugs - Clinton, Alex J.; Pollini, Robin A. (Frontiers in Psychology, 2021)
People who inject drugs are often the target of stigma that puts this already at-risk group at greater risk of harm. Past research has shown that holding stigmatizing views of people who inject drugs increases risky behaviors and is a barrier to their engagement in important medical and public health interventions. One explanation is that the negativity surrounding the group causes increased levels of anticipated emotional exhaustion, discouraging positive engagement. However, there has been minimal research focused on addressing this negativity to reduce levels of held stigma against people who inject drugs. We hypothesized that giving people an imagined positive contact exercise about people who inject would lead to a reduction in stigma, since exposure to positive empathy may create new mental associations between stigmatized groups and more positive emotions and experiences. Secondarily, we hypothesized that positive empathy strategies would be more effective than traditional ignorance reduction techniques, and that the latter would be more effective than a control condition. Our sample consisted of 375 participants recruited online. Participants were assigned to one of three study conditions: a positive empathy condition, an ignorance reduction condition, or a control condition, and completed a posttest social distance measure. Results demonstrated that subjects exposed to the positive empathy stigma reduction condition experienced a significant reduction in held stigma while participants exposed to traditional ignorance reduction techniques showed no significant reduction in held stigma. Positive empathy-based stigma interventions should be further researched as a promising avenue to reduce the effects of drug-related stigma.